Korelasi Minat Belajar Matematika Dan Lingkungan Belajar Terhadap Prestasi Belajar TIK (Studi Kasus : SMA Saraswati Singaraja) - Ayu Anden Decy Apsari, I Dewa; Seri Wahyuni, Dessy; Mahendra Darmawiguna, I Gede (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study aimed to determine (1) the relationshipbetween interest in learning mathematics achievement of highschool students studying Information and CommunicationTechnologies (ICT) Saraswati Singaraja, (2) the relationshipbetween the learning environment for high school students’learning achievement of high school students studying Informationand Communication Technologies (ICT) Saraswati Singaraja, andthe relationship between interest in learning mathematics andlearning environment together towards achievement of high schoolstudents studying Information and Communication Technologies(ICT) Saraswati Singaraja. This type of research is ex post facto,wich consist of two variables independent variables and onedependent variable. The samples in this research were 130 people.Data for interest in learning mathematics and the learningenvironmet were collected through questionnaires interest inlearning mathematics and the learning environment, while theInformation and Communication Technologies (ICT) learningachievement data obtained through the high school gradesInformation and Communication Technologies (ICT) SaraswatiSingaraja odd semester of academic year 2012/2013. The collecteddata were analyzed using parametric statistical test prerequisitenormality, linearity and regression toward significance, andmulticollinearity. The result showed that : (1) interest in learningmathematics has a positive and sigificant relationship on studentachievement by 0,891 ICTs are categorized as very strong with acontribution of 79,46%, (2)learning environment has a positive andsignificant relationship to the achievement of ICT of 0,565 wich arecategorized with a contribution of 31,88%, and (3) interest inlearning mathematics and learning environment together have apositive and significant relationship to learning achievement by0,916 ICTs are categorized strong influence with a contribution of83,87%.